Pemanfaatan Saliva dalam Mendeteksi Faktor-Faktor Resiko terhadap Karies - Edi Hartini Sundoro (Faculty of Dentistry, Universitas Indonesia, 2015)
Salia can be used to detect several diseases including caries. In conservative dentistry, examinations of saliva to risk factors for caries has been developed. This is partly due to the fact that treatment of caries lesions has been shifted to a preventive approach. Examinations of salivary flow, buffer capacity and laboratory tests for Lactobacillus and Streptococcus mutans will be reviewed.